Isolation and characterization of Streptococcus spp. from dental plaque samples - Wagiman, Zatul Najihah (2015)
Dental caries is a prevalent oral disease worldwide. It affects a vast majority of adults, including those in developed countries although many prevention measures are available. It is of great importance to update the dental caries status of adults and to investigate the utilization of dental services and dental caries experience from publics. It is also important to know the exact bacteria species that involves in the dental plaque formation especially the bacteria that form biofilm. In conjunction with that, this study was conducted to isolate the bacteria from oral cavity and to characterize and identify them. Dental plaque samples were collected from 15 female subjects aged between 20 – 25 years old. Early assumption can be made based on colony morphology, Gram staining and biochemical tests that the bacteria isolated were Streptococcus spp. Only two isolates were successfully identified as Streptococcus salivarius based on 16s rDNA sequencing.